The Role of Local Journalists in Covering Black Campaign News during the 2024 Banten Gubernatorial Election - Fhatihah, Ida Nurul; Trianita, Yanti (COMMUSTY Journal of Communication Studies and Society, 2025)
Indonesia is a democratic country that upholds public participation in elections.During the 2024 Banten Gubernatorial Election, Black Campaigns targeting candidate pairs emerged and posed a threat to the quality of democracy. Digital media played a significant role in the dissemination of political issues, while local journalists were required to maintain professionalism and objectivity. This study aims to explore the roles, challenges, and strategies of local journalists in covering Black Campaign issues. Using Kurt Lewin’s Gatekeeping Theory, the research was conducted through a descriptive qualitative approach with a post-positivist paradigm. The findings indicate that local journalists play a crucial role in maintaining the quality of factual and balanced information despite facing political pressure, social norms, and the dynamics of digital media. The challenges encountered are both technical and social, including public pressure, media algorithm influence, and strong local cultural values. These pressures do not directly alter news content but influence its presentation style to remain ethical and acceptable to the public. To maintain neutrality, journalists apply strict editorial strategies, data verification, and maintain professional distance from sources. Despite external influences from institutions such as the Press Council, the General Elections Commission (KPU), and the Election Supervisory Board (Bawaslu), journalists adhere to journalistic codes of ethics and existing official regulations.